STRUKTUR GEOLOGI PALEOGEN DAN NEOGEN DI JAWA BARAT - -, Iyan Haryanto (Fakultas Teknik Geologi Universitas Padjadjaran, 2006)
Regional Structure in Java influenced by collision between Hindia-Australia plate and Eurasi plate activities. This collision formed mélange rock that now outcropped in Ciletuh, Sukabumi. Beside mélange rock are found, this collision form regional structure of in Java both under and also above surface.Under surface Structure generally expand from southern part of Java continent to Java Sea. This North-south Structure can be classified as Sunda Pattern. Other Regional Structural Geology can be seen on the surface of either direct field perception and also from satellite imagenary, for example Cimandiri fault, Baribius fault and Lembang fault. Cimandiri fault represent Meratus pattern while Baribis fault and lembang fault represent Java pattern.The forming of this three fault pattern also followed by volcanic activities along with continental plates collision activities. The Changes of volcanic belts in are related to the subduction belt changes or the changes of subduction zone angle. These changes also influence regional structural geology in West Java.